Minocycline Prevents the Development of Mechanical Allodynia in Mouse Models of Vincristine-Induced Peripheral Neuropathy - Starobova, H.; Mueller, A.; Allavena, R.; Lohman, R. J.; Sweet, M. J.; Vetter, I. (Frontiers in Neuroscience, 2019)
Vincristine is an antineoplastic substance that is part of many chemotherapy regimens, used especially for the treatment of a variety of pediatric cancers including leukemias and brain tumors. Unfortunately, many vincristine-treated patients develop peripheral neuropathy, a side effect characterized by sensory, motoric, and autonomic symptoms. The sensory symptoms include pain, in particular hypersensitivity to light touch, as well as loss of sensory discrimination to detect vibration and touch. The symptoms of vincristine-induced neuropathy are only poorly controlled by currently available analgesics and therefore often necessitate dose reductions or even cessation of treatment. The aim of this study was to identify new therapeutic targets for the treatment of vincristine-induced peripheral neuropathy (VIPN) by combining behavioral experiments, histology, and pharmacology after vincristine treatment. Local intraplantar injection of vincristine into the hind paw caused dose- and time-dependent mechanical hypersensitivity that developed into mechanical hyposensitivity at high doses, and lead to a pronounced, dose-dependent infiltration of immune cells at the site of injection. Importantly, administration of minocycline effectively prevented the development of mechanical hypersensitivity and infiltration of immune cells in mouse models of vincristine induce peripheral neuropathy (VIPN) based on intraperitoneal or intraplantar administration of vincristine. Similarly, Toll-like receptor 4 knockout mice showed diminished vincristine-induced mechanical hypersensitivity and immune cell infiltration, while treatment with the anti-inflammatory meloxicam had no effect. These results provide evidence for the involvement of Toll-like receptor 4 in the development of VIPN and suggest that minocycline and/or direct Toll-like receptor 4 antagonists may be an effective preventative treatment for patients receiving vincristine.